Research for development of animal traction in West Africa. Proceedings of the fourth workshop of the West African Animal Traction Network - Lawrence, P.R.; Lawrence, K.; Dijkman, J.T.; Starkey, P.H. (International Livestock Centre for Africa, 1993)
The report is divided in 12 sections. The first section is introductory. The second section presents research on animal health of working animals. Diversified uses of animal traction including animal-powered rice-huller, weed control are discussed in the 3rd section. The fourth section looks into harnessing and implements used in the different regions of West Africa. The management and nutrition of working animals is discussed in the fifth and sixth sections. Experimental methods in draught animal research is presented in section seven and socio economic aspects of animal traction research are dealt in section eight. Section nine looks into technology transfer to the rural community. The rest of the sections include workshop synthesis, poster abstracts and miscellaneous discussions.